Programa de desentrenamiento deportivo para la reducción de los efectos fisiológicos de las marchistas olímpicas de la ciudad de Loja, 2012-2016. - Tacuri Ordóñez, Chesman Adrián (2024)
The present curricular integration work was developed with the aim of elaborating a sports detraining program for the reduction of the physiological effects of the Olympic walkers of Loja, 2012-2016; in addition, a mixed approach was used with a quasi-experimental design and correlational scope supported by inductive, deductive and analytical methods. Diagnostic instruments such as a survey and test were applied to a sample of 2 participants. According to the results, once the diagnostic instruments were applied, it´s evident that the Olympic walkers in the first phase of application of the cooper pre-test have a good evaluation according to the test indicators, covering an average distance of 2615 meters. Based on the indicators of the pre-test, a pedagogical proposal was designed and elaborated based on a sports detraining program for the reduction of the physiological effects, which was structured in 8 weeks, being a daily training session from Monday to Friday in the morning hours with work related to the training applied in athletics and after the application of the post test of cooper, both athletes increased their distance covered reaching an average of 2800m, continuing in a good evaluation, but improving their Vo2 max. It is concluded that before the application of the program there were certain gaps in aspects such as doubts or questions about the program, motivation, commitment, self-improvement and the role to be fulfilled by the athletes in their activities, however, after the application of the program their physical condition improved in these aspects because they were not fit from having been Olympic athletes, thus demonstrating the effectiveness of the reduction of these physiological effects by lowering their basal pulse, improving their metabolism and body weight. Key words: sports training, detraining, reduction of physiological effects.